Penetrating Bladder Trauma: A High Risk Factor for Associated Rectal Injury - B. M. Pereira; L. O. Reis; T. R. Calderan; C. C. de Campos; G. P. Fraga (Advances in Urology, 2014)
Demographics and mechanisms were analyzed in prospectively maintained level one trauma center database 1990–2012. Among 2,693 trauma laparotomies, 113 (4.1%) presented bladder lesions; 51.3% with penetrating injuries (n=58); 41.3% (n=24) with rectal injuries, males corresponding to 95.8%, mean age 29.8 years; 79.1% with gunshot wounds and 20.9% with impalement; 91.6% arriving the emergence room awake (Glasgow 14-15), hemodynamically stable (average systolic blood pressure 119.5 mmHg); 95.8% with macroscopic hematuria; and 100% with penetrating stigmata. Physical exam was not sensitive for rectal injuries, showing only 25% positivity in patients. While 60% of intraperitoneal bladder injuries were surgically repaired, extraperitoneal ones were mainly repaired using Foley catheter alone (87.6%). Rectal injuries, intraperitoneal in 66.6% of the cases and AAST-OIS grade II in 45.8%, were treated with primary suture plus protective colostomy; 8.3% were sigmoid injuries, and 70.8% of all injuries had a minimum stool spillage. Mean injury severity score was 19; mean length of stay 10 days; 20% of complications with no death. Concomitant rectal injuries were not a determinant prognosis factor. Penetrating bladder injuries are highly associated with rectal injuries (41.3%). Heme-negative rectal examination should not preclude proctoscopy and eventually rectal surgical exploration (only 25% sensitivity).